# let f: R ---> R+ and g: --> R+ . R be defined as f(x) = ex and g(x) = lnx.let f: R ------> R+ and g: -------->...

let *f***: R ---> R+** and *g***: --> R+** . **R** be defined as **f(x) = ex and g(x) = lnx.**

let *f***: R ------> R+** and *g***: --------> R+** **R** be defined as **f(x) = ex and g(x) = lnx.**

Show that f and g are inverse of each other.

### 1 Answer | Add Yours

You need to follow the steps of procedure of finding the inverse of a function such that:

You need to substitute y for f(x) such that:

`y = e^x`

You need to substitute y for x and x for y such that:

`x = e^y`

You need to solve for y the equation x = e^y, hence you should take logarithms both sides such that:

`x = e^y`

`ln x = ln (e^y)`

You need to use power property of logarithms such that:

`ln x = y*ln e`

You need to remember that `ln e = 1` such that:

`ln x = y`

**Notice that the last line represents the function g(x) = ln x, hence, the function g(x) expresses the inverse of function f(x).**